SCIENTIFIC-TECHNOLOGICAL COOPERATION BETWEEN ARGENTINA AND CHINA: A STUDY ON THE ARGENTINE-CHINESE CENTER FOR FOOD SCIENCE AND TECHNOLOGY (2008-2019) - López, María Paz (2022)
The article is framed on the theme of international scientific-technological cooperation and analyzes the emergence, objectives, projects, scope and limitations of the Argentine-Chinese Center for Food Science and Technology, whose creation protocol was signed in 2008 by the Ministry of Science, Technology and Productive Innovation of the Argentine Republic and the Ministry of Science and Technology of the People’s Republic of China. For this, it recovers voices of key actors and contemplates the broader framework of scientific-technological policy, foreign policy and bilateral relations of the countries involved. The study runs until 2019 and uses contributions on the subject, official documents and interviews with directors of binational projects. Among the results, it has been observed that, with its limitations, the initiative advanced in the generation of ties and joint activities between the partners, developing bilateral scientific-technological projects on relevant topics, within the framework of broader technological, commercial and diplomatic objectives.